(untitled) (Nordic Journal of African Studies, 1999)
Banditry that cannot be categorized as traditional feuding has failed to attract international scholarship despite its pervasiveness and devastation to an already politically fragile Horn of Africa. This article decries the lack of scholarly interest on the subject, which it links to the treatment of the problem as a concern purely for the Third World, and the United Nations ineffectiveness in dealing with subnational tensions. While there is a general academic draught on the subject, some of the existing literature romanticizes the brigand and fails to establish a firm anchor of the phenomenon with geopolitical issues that wrap together poverty, political instability and inexorable lawlessness. Therefore this article briefly addresses this gap in our knowledge of organized banditry whose motive, opportunity, and means though manifested within the State, are actually symptoms of regional problems. It traces the causes, history, and implications of four families of brigands, Kafagne, Faloul, Ngoroko, and the Shifta found in the turbulent Horn of Africa today. In the concluding reflections, several measures are recommended for the regional governments and the international society to eradicate the problem.